2008
DOI: 10.1002/jcu.20526
|View full text |Cite
|
Sign up to set email alerts
|

Thanatophoric dysplasia: Role of 3‐dimensional sonography

Abstract: Purpose. Fetal thanatophoric dysplasia (TD) is a lethal skeletal dysplasia. Therefore, antenatal diagnosis of TD is mandatory in routine obstetrical care. However, because TD is relatively rare, prenatal detection is not an easy task. In the past, 2-dimensional (2D) sonography had been applied as the mainstay of prenatal diagnosis of TD. In this series, we report our work of detecting TD using 3-dimensional (3D) sonography.Methods. We reviewed our computer database of prenatal diagnosis of TD in National Cheng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…3D-US is complementary to 2D-US, but more accurate in demonstrating subtle facial features and for measuring distances, angles and sizes in defined anatomical planes. Several authors suggest that 3D-US improves the accuracy of prenatal diagnosis of skeletal disorders [67][68][69][70]73 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3D-US is complementary to 2D-US, but more accurate in demonstrating subtle facial features and for measuring distances, angles and sizes in defined anatomical planes. Several authors suggest that 3D-US improves the accuracy of prenatal diagnosis of skeletal disorders [67][68][69][70]73 .…”
Section: Discussionmentioning
confidence: 99%
“…Many other 3D-US studies have described various features of the fetal cranium, both normal and abnormal 5,6,[62][63][64][65][66] . Any decision to use 3D-US for bone imaging should be based on its potential diagnostic value, and some investigators have reported improved characterization of fetal bone disorders [67][68][69][70] .…”
Section: Craniosynostosismentioning
confidence: 99%
“…Thanatophoric dysplasia (TD) is the most common lethal form of skeletal dysplasias in fetuses and the affected neonates usually die shortly after birth [1]. The term thanatophoric in Greek means ''death bearing'' [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although this specific feature is well known in the pathology literature, an awareness of the sonographic appearance of TLD on prenatal ultrasound is limited as compared with the better known musculoskeletal features. Recent publications and clinical practice guidelines have failed to discuss TLD as a potential diagnostic marker for TD. Given that the current prenatal diagnostic accuracy of TD ranges from 40% to 87.5%, detection of TLD on prenatal ultrasound could provide added specificity in patient counseling and guide molecular investigations.…”
Section: Introductionmentioning
confidence: 99%